Pharmacokinetics and Pharmacodynamics of Colistin Combined With Isopropoxy Benzene Guanidine Against mcr-1-Positive Salmonella in an Intestinal Infection Model - Kong, Lingli; Lu, Yixing; Yang, Liuye; Zhang, Wanying; Zuo, Beini; Peng, Xianfeng; Qin, Zonghua; Li, Miao; Zeng, Zhenling; Zeng, Dongping (Frontiers in Microbiology, 2022)
Plasmid-borne colistin resistance mediated by mcr-1 may contribute to the dissemination of resistant Gram-negative bacteria. Here, we found a guanidine compound, namely, isopropoxy benzene guanidine (IBG), which boosted the efficacy of colistin against mcr-1-positive Salmonella. This study aimed to develop a pharmacokinetics/pharmacodynamics (PK/PD) model by combining colistin with IBG against mcr-1-positive Salmonella in an intestinal infection model. PK studies of colistin in the intestine were determined through oral gavage of single dose of 2, 4, 8, and 16 mg/kg of body weight in broilers with intestinal infection. On the contrary, PD studies were conducted over 24 h based on a single dose ranging from 2 to 16 mg/kg. The inhibitory effect Imax model was used for PK/PD modeling. The AUC0-24h/MIC index was used to evaluate the relationship between PK and PD, and the correlation was >0.9085. The AUC0-24h /MIC targets in combination required to achieve the bacteriostatic action, 3-log10 kill, and 4-log10 kill of bacterial counts were 47.55, 865.87, and 1894.39, respectively. These results can facilitate the evaluation of the use of IBG as a colistin adjuvant in the treatment of intestinal diseases in broilers caused by colistin-resistant bacteria.